2008
DOI: 10.1007/s10562-008-9715-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Polymer Nanospheres Immobilizing Metalloporphyrins. Catalysis and Reuse to Hydroxylate Cyclohexane with Molecular Oxygen

Abstract: Magnetic polymer nanospheres immobilizing Co(II) porphyrin or Mn(III) porphyrin were synthesized and their catalytic activities in hydroxylating cyclohexane were comparably investigated. The catalytic results have shown that these magnetic nanospheres are highly efficient and recyclable catalysts and the nanospheres with Mn(III) porphyrin are more active than those with Co(II) porphyrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Though magnetic polymer microspheres immobilizing metalloporphyrins have been reported and the catalytic results in the cyclohexane oxidation with molecular oxygen have shown that these magnetic microspheres are highly efficient and recyclable catalysts [7,8], the preparation of the magnetic Fe 3 O 4 nanoparticle bonded metalloporphyrins is still unprecedented. Due to the surface properties of magnetic iron oxide nanoparticles, especially chemically stable silica-coated Fe 3 O 4 nanoparticles, organosilane is often used as a good medium to covalently bond organic compounds with magnetic nanoparticles.…”
Section: Synthesis and Characteration Of Nanoparticle Bonded Metallopmentioning
confidence: 99%
See 1 more Smart Citation
“…Though magnetic polymer microspheres immobilizing metalloporphyrins have been reported and the catalytic results in the cyclohexane oxidation with molecular oxygen have shown that these magnetic microspheres are highly efficient and recyclable catalysts [7,8], the preparation of the magnetic Fe 3 O 4 nanoparticle bonded metalloporphyrins is still unprecedented. Due to the surface properties of magnetic iron oxide nanoparticles, especially chemically stable silica-coated Fe 3 O 4 nanoparticles, organosilane is often used as a good medium to covalently bond organic compounds with magnetic nanoparticles.…”
Section: Synthesis and Characteration Of Nanoparticle Bonded Metallopmentioning
confidence: 99%
“…These results indicated that it is natural choice for cytochrome P-450 mono-oxygenase with ironporphyrin structure [6]. Ji et al [7,8] have attempted to immobilize metalloporphyrins on magnetic Fe 3 O 4 nanoparticles by copolymerizing styrene with metalloporphyrins in the presence of Fe 3 O 4 magnetic fluid, and the obtained magnetic polymer microspheres immobilizing metalloporphyrins in the cyclohexane oxidation with molecular oxygen could be easily separated and recovered with the aid of a magnet. Nevertheless, under geomagnetic field (5 9 10 -5 T), the influence of the saturation magnetizations of magnetic Fe 3 O 4 nanoparticles on the catalytic abilities of metalloporphyrins remains to be highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic aerobic hydroxylation of cyclohexane was carried out at 30.0 ± 0.1°C in a Schlenk flask [13,[17][18][19][20][21][22][23][24]]. The catalytic system consisted of catalyst [copolymersupported porphyrinatomanganese(III), alkylated copolymersupported porphyrinatomanganese(III) or non-supported porphyrinatomanganese(III)], cyclohexane (5.55 mmol), coreductant (1.1 mmol ascorbate, 4.0 910 -2 mmol thiosalicylic acid), acetone/water (9:1, 10 mL), and pure oxygen (101 kPa).…”
Section: Catalytic Experiments For Cyclohexane Hydroxylationmentioning
confidence: 99%
“…We have previously immobilized some metalloporphyrins on polystyrene-based supports, such as Merrifield's resin, and studied their catalytic activities in cyclohexane hydroxylation [16,17]. Recently, we focused on a new method to synthesize polystyrene-based supports for metalloporphyrins as catalysts for the hydroxylation of cyclohexane, and styrene-methylacrylic acid copolymer microspheres were prepared [18][19][20]. In this paper, we report another new synthetic method for polystyrene-based supports to immobilize metalloporphyrins.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [11,12] employed magnetic polymer nanospheres (with Fe 3 O 4 core and polystyrene shell) as a support of metalloporphyrin. It was found that these nanospheres have good magnetic responsiveness and thus can be recycled by employing an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%